SPECIFICITY OF LOGOPEDICAL ASSISTANCE FOR CHILDREN IN THE HEALTH CARE SYSTEM - Korposh, V. (SWorld-Ger Conference proceedings, 2023)
The state of speech disorders in children at the present stage and the network of institutions and facilities providing speech therapy are highlighted. The peculiarities of providing speech therapy in health care institutions of Ukraine are identified and